Unilateral Ophthalmoplegia in Delirium Tremens Patient Due to Subdural Hematoma - Limbu, Suren; K.C., Bipin; Regmi, Binita; Chaudhary, Santosh (Journal of Psychiatrists' Association of Nepal, 2022)
Ophthalmoplegia or the paralysis of nerves supplying extraocular muscles can be due to numerous etiologies. In alcohol users, ophthalmoplegia might be due to Wernicke's encephalopathy. A high dose of thiamine should be used with a high index of suspicion in such cases, but at the same time, other life-threatening conditions should not be missed. Careful history taking, clinical features and neuro imaging can guide in identifying the likely aetiology. Here, we present a case of isolated unilateral oculomotor nerve palsy due to subdural hematoma in a patient with delirium tremens.